Transesterification of biodiesel byproduct glycerol and dimethyl carbonate over porous biochar derived from pyrolysis of fishery waste. (1st June 2018) - Shikhaliyev, K.; Okoye, P.U.; Hameed, B.H.
Highlights: Fishmeal biochar is a potential catalyst for glycerol carbonate (GC) synthesis. Biochar catalyzed glycerol transesterification with DMC to 99% GC yield. Solvent addition sustains five reusability cycles with more than 92% GC yield. Abstract: Glycerol carbonate (GC), an oxygenated fuel additive was synthesized from oversupplied glycerol in transesterification with dimethyl carbonate (DMC) over fishmeal biochar. Fishmeal was carbonized at various temperatures (550–750 °C). The most suitable carbonization temperature based on GC yield was utilized in transesterification. Biochar was characterized to investigate textural and basic properties and surface functional groups. Thermal treatment, methanol washing, and solvent addition techniques were adopted to investigate biochar reusability after each reuse. At the most suitable reaction conditions of 85 °C, 2 wt% catalyst dosage, and DMC-to-glycerol molar ratio of 2, 99.5% GC yield and complete conversion of glycerol were attained over biochar carbonized at 650 °C. Strong basicity of biochar initiated decarboxylation reaction, which resulted in formation of glycidol (0.5%). Addition of methanol without catalyst treatment after each reuse sustained GC yield of 93% at the end of fifth reuse.